Triglyceride-glucose index predicts ventricular aneurysm formation in acute ST-segment elevation myocardial infarction - Zeng, Xiaobin; Zhang, Yanyu; Xie, Xiaoshuang; Lan, Jianjun; Li, Shiyang (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride–glucose (TyG) index has been confirmed to be a predictor of cardiovascular diseases. The present study aimed to assess the predictive value of TyG index for left ventricular aneurysm (LVA) formation and prognosis in patients with acute ST-segment elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (PCI).MethodsThis prospective study included 991 patients with acute STEMI who underwent primary PCI. Multivariable logistic regression and receiver operating characteristic (ROC) curve analysis were used to assess the predictive value of TyG index for LVA formation. Prognosis analysis was performed with cox proportional hazard regression.ResultsThe prevalence of LVA was 14.4%. A higher TyG index was associated with a greater incidence of LVA (23.1% vs. 11.8%, P< 0.001). The TyG index was also higher in the LVA group than in the non-LVA group (9.4 ± 0.9 vs. 9.0 ± 0.8, P<0.001). Multivariable logistic regression analysis revealed that the TyG index was independently associated with the risk of LVA [odds ratio (OR)= 2.4, 95% confidence interval (CI)= 1.51-3.82, P< 0.001]. The predictive value of the TyG index remained significant even after cross-validation by dividing the study population into a training set (OR= 2.32, 95% CI= 1.24-4.35, P= 0.009) and validation set (OR= 3.19, 95% CI= 1.42-7.19, P= 0.005). Higher TyG index was correlated with increased risk of cardiac death (HR= 2.17, P= 0.04). The maximal length and width of LVA were significantly increased in patients with TyG index ≥ 9.68 compared with < 9.68 (P< 0.001). The discriminant power of TyG index for LVA was 0.742, which was superior to both triglyceride (C statistic= 0.666) and fasting blood glucose (C statistic= 0.613). The combination of TyG index, left ventricular ejection fraction, gensini score, and left anterior descending artery as the culprit vessel could significantly improve the predictive ability (C statistic= 0.908).ConclusionsA higher TyG index was an independent predictor for LVA formation and increased risk of cardiac death in patients with STEMI who underwent primary PCI.